Comparative thermal response of CoCrMnFeNi high entropy alloy and alumina under multi-pulse laser heating - Nosakhare J. Aigbedion (Results in Materials)
High Entropy Alloys (HEAs) are relatively new material with remarkable mechanical properties which allow them to have diverse industrial applications. On the other hand, Alumina is an extensively studied ceramic material which has shown usefulness in aerospace, automobile, medical and electronics, however, its fracture toughness is often a major limitation.Conventional machining process often result in dimensional inaccuracies, thermal damages to material surface as well as subsurface cracks. Laser surface treatment of materials has been explored as an alternative machining process for better dimensional accuracy, maintenance of material integrity and enhancement of material properties. However, different materials possess different mechanical properties which impacts their response to laser heating. In this study, a multi-pulse laser heating computational model based on COMSOL Multiphysics was developed to study the thermal response of CoCrMnFeNi HEA and Alumina under surface laser heating and different laser power magnitude. A comparative analysis was implemented using the temperature profiles, isothermal contours and von Mises stress of both materials. The obtained results reveal that under similar laser heating conditions, Alumina attains higher temperatures and is relatively limited in efficiently dissipating the deposited heat. The thermal expansion limitations of Alumina under laser heating reveals that the material is more likely to undergo thermal cracking or fracture before plastic deformation while CoCrMnFeNi HEA will more likely undergo plastic deformation before failure.